High-transmittance weather-resistant impact-resistant color striped board and manufacturing method

CN120963174BActive Publication Date: 2026-10-30DAFENG JIANGNAN MACHINERY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511117544.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-11
Publication Date
2026-10-30
Estimated Expiration
2045-08-11

AI Technical Summary

Technical Problem

本发明通过材料组分的协同作用和多层共挤工艺,有效解决传统板材力学性能与透光性能难以兼顾的问题,适用于高要求装饰和功能性应用

Benefits of technology

[0027]1、本发明通过PC与PBAT的共混,借助钛酸四丁酯促进界面相容性,形成化学键合的共聚物,显著提升基体层的刚性;熔融过程中引发剂的微交联进一步增强层间结合力,相较于现有技术,本发明通过MBS和多层结构设计,避免了刚性材料韧性不足的缺陷,后续工艺过程释放内应力,改善分子链排列,减少微裂纹,确保材料在高负荷下仍保持优异刚性,适用于建筑装饰和汽车内饰等高强度应用场景。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120963174B_ABST
    Figure CN120963174B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of multilayer structure, in particular to a high-transparency weather-resistant impact-resistant color stripe plate and a manufacturing method. The present application overcomes the problem that the mechanical properties and optical properties of the color stripe plate in the prior art cannot be considered simultaneously. The present application adopts a multilayer structure, from top to bottom, a weather-resistant layer, a base layer and a weather-resistant layer, and a stripe layer penetrating the interface between the weather-resistant layer and the base layer; the base layer is obtained by melt copolymerization of polycarbonate, PBAT and MBS; the weather-resistant layer is obtained by melt of polymethyl methacrylate, polycarbonate, maleic anhydride grafted polycarbonate and ultraviolet absorber; the stripe layer is prepared by stepwise mixing of weather-resistant PC, modified nano titanium dioxide and composite inorganic pigment, and a multi-channel distributor is used to form fine stripes. Through the synergistic effect of material components and the multilayer co-extrusion process, the present application effectively solves the problem that the mechanical properties and light transmission properties of traditional plates are difficult to consider simultaneously, and is suitable for high-performance building decoration.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of multi-layer structure technology, specifically to a high-transmittance, weather-resistant, and impact-resistant colored striped plate and its manufacturing method. Background Technology

[0002] Polycarbonate sheets are a new type of material with high light transmittance, impact resistance, and aging resistance. They are widely used in industrial safety partitions and municipal traffic safety partitions. However, due to their excellent transparency, they are not easily observed by pedestrians when used in industrial and municipal safety partitions. This can easily lead to injuries such as collisions, scratches, and falling fragments caused by impacts, without fundamentally reducing safety hazards.

[0003] Existing colored striped panels, especially those used in construction and decoration, often face the challenge of balancing mechanical and optical properties. Traditional single-layer blended panels require direct mixing of pigments and polymer matrices to achieve the colored stripe effect; however, this blending method easily leads to uneven pigment dispersion and the formation of agglomerates. This not only affects the clarity and aesthetics of the stripes but also significantly reduces the panel's light transmittance due to enhanced light scattering. Furthermore, pigment agglomerates create stress concentration points within the material, resulting in decreased toughness and impact strength under impact.

[0004] Furthermore, in existing technologies, toughening agents are typically added to improve mechanical properties, especially impact strength. However, this may sacrifice the material's rigidity or transparency, leading to an imbalance in performance. Therefore, the main problem limiting the application range of colored striped sheets is how to design material systems and processing techniques that maintain the high light transmittance and clear stripes of the sheet while also considering its comprehensive mechanical properties.

[0005] To address this, a high-transmittance, weather-resistant, and impact-resistant colored striped plate and its manufacturing method are proposed. Summary of the Invention

[0006] The purpose of this invention is to provide a high-transmittance, weather-resistant, and impact-resistant colored striped sheet and its manufacturing method. This invention employs a multi-layer structure, consisting of a weather-resistant layer, a substrate layer, and another weather-resistant layer from top to bottom, with the stripe layer extending through the interface between the weather-resistant layer and the substrate layer. The substrate layer is obtained by melt copolymerization of polycarbonate, PBAT, and MBS. The weather-resistant layer is obtained by melt-polymerization of polymethyl methacrylate, polycarbonate, maleic anhydride-grafted polycarbonate, and a UV absorber. The stripe layer is prepared by stepwise mixing of weather-resistant PC, modified nano-titanium dioxide, and composite inorganic pigments, and fine stripes are formed using a multi-channel distributor. This invention effectively solves the problem of balancing mechanical properties and light transmittance in traditional sheet materials through the synergistic effect of the material components and the multi-layer co-extrusion process, making it suitable for high-requirement decorative and functional applications.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] This invention provides a method for manufacturing a high-transmittance, weather-resistant, and impact-resistant colored striped plate, comprising the following manufacturing steps:

[0009] From top to bottom, the layers are a weather-resistant layer, a base layer, and another weather-resistant layer. The base layer is added to the main extruder and melt-extruded to obtain the base layer melt. The weather-resistant layer is added to the satellite extruder and melt-extruded to obtain the weather-resistant layer melt. The striped layer is added to the small extruder and melt-extruded to obtain the striped layer melt. At the end of the homogenization section of the main extruder, dicumyl peroxide is precisely injected as an initiator via a metering pump at a dosage of 0.15% of the total mass of the base layer. The weather-resistant layer melt, the base layer melt, and the weather-resistant layer melt are then fed into a multi-channel distributor to form a three-layer structure. Simultaneously, the striped layer melt is divided into multiple streams by the distribution channels within the distributor and injected into the main extruder. A composite melt is obtained by mixing the weather-resistant layer melt and the base layer melt; the composite melt is then fed into a die head, and the temperature is maintained at 250-260℃ to obtain a multi-layer melt; the multi-layer melt is fed into a three-roll calender, with the temperatures of the three rolls controlled at 110℃, 125℃, and 130℃ respectively. The thickness of the sheet is precisely controlled by the gap between the rolls, and preliminary shaping and cooling are performed to obtain the sheet precursor; the sheet precursor is then passed through an online annealing furnace, slowly heated to 125-130℃, and held for 20-30 minutes; it is then slowly cooled to below 60℃ at a cooling rate of 1-2℃ / min, and finally air-cooled to room temperature to obtain a colored striped sheet;

[0010] The matrix layer is obtained by melt copolymerization of polycarbonate and polybutylene terephthalate-adipate, and by melt extrusion of MBS and additives.

[0011] The weather-resistant layer is obtained by melt extrusion of polymethyl methacrylate and polycarbonate;

[0012] The striped layer is obtained by melt extrusion of weather-resistant PC, modified nano-titanium dioxide, and composite inorganic pigments.

[0013] Preferably, the layered structure is a symmetrical three-layer design of weather-resistant layer / substrate layer / weather-resistant layer. The striped layer is embedded in the upper and lower weather-resistant layers in the form of 8-12 streams, with an embedding depth of 1 / 3 of the thickness of the weather-resistant layer. The stripe width is precisely controlled to be 1-3mm and the spacing is 5-10mm through the micro-channel and nozzle design of the distributor to ensure a uniform decorative effect. The weather-resistant layer is 0.5-1.0mm thick and the substrate layer is 2-3mm thick.

[0014] Preferably, the striped layer melt is divided into multiple streams through 8-12 microporous channels of the flow divider plate, and the flow rate is precisely controlled at 0.5-1.0 kg / h by a metering pump; each stream is injected into the weather-resistant layer / substrate layer interface at an angle of 15-30° through the nozzle of the distribution channel.

[0015] Preferably, the fabrication of the substrate layer includes the following steps:

[0016] By mass, 70-80 parts of polycarbonate and 15-25 parts of polybutylene terephthalate (PET) were placed in a vacuum drying oven and dried at 80°C for 4 hours to obtain a dried raw material. The dried raw material was then added to a twin-screw extruder, along with 0.3-0.5 parts of tetrabutyl titanate. The melt temperature was 250-260°C, and the screw speed was 200-300 rpm. The mixture was melt copolymerized for 10-20 minutes to obtain a copolymer. 5-10 parts of MBS, 0.3 parts of antioxidant 1010, and 0.5 parts of zinc stearate were added to the copolymer. The feeding section temperature was 180-220°C, the compression section temperature was 240-260°C, the metering section temperature was 245-255°C, and the die head temperature was 240-250°C. The screw speed was maintained at 300-450 rpm to obtain the matrix layer. The melt index of the matrix layer was 8-10 g / min.

[0017] Preferably, the manufacturing of the weather-resistant layer includes the following steps:

[0018] 50-60 parts of polymethyl methacrylate and 35-45 parts of polycarbonate were placed in a vacuum drying oven and dried at 90℃ for 4 hours to obtain dried material. The dried material was then added to a twin-screw extruder, along with 3-5 parts of maleic anhydride-grafted polycarbonate, 0.5 parts of UV absorber-326, 0.5 parts of UV absorber 1600, 0.8 parts of HALS, and 0.5 parts of zinc stearate. The feeding section temperature was 180-210℃, the compression section temperature was 230-250℃, the metering section temperature was 230-240℃, and the die head temperature was 220-230℃. The screw speed was maintained at 300-400 rpm to obtain a weather-resistant layer with a melt index of 6-8 g / min.

[0019] Preferably, the manufacturing of the stripe layer includes the following steps:

[0020] Place 80-90 parts of weather-resistant PC in a vacuum drying oven and dry at 80℃ for 4 hours to obtain a dried system. Add the dried system to a high-speed mixer, add 5-8 parts of modified nano-titanium dioxide, and stir for 5 minutes at a speed of 500-600 rpm to obtain a mixture. Add 8-12 parts of composite inorganic pigment to the mixture, and stir for 10 minutes at a speed of 300-400 rpm to obtain a mixed system. Add 0.6 parts of polyether dispersant, 0.5 parts of zinc stearate, and 0.3 parts of antioxidant 1010 to the mixed system, and then add it to a twin-screw extruder. During the discharge process, the temperature of the feeding section is maintained at 190-220℃, the temperature of the compression section at 250-270℃, the temperature of the metering section at 250-260℃, and the temperature of the die head at 245-255℃. The screw speed is maintained at 200-400 rpm to obtain the striped layer. The composite inorganic pigment is obtained by mixing titanium dioxide and iron oxide red in a certain mass ratio. The specific mass ratio can be adjusted according to the specific color requirements. During the mixing process, the ball-to-material ratio is maintained at 10:1 in a ball mill, the ball mill speed is 300-500 rpm, and the ball milling time is 2-4 hours.

[0021] Preferably, the stepwise blending includes the following steps:

[0022] Place 80-90 parts of weather-resistant PC in a vacuum drying oven and dry at 80℃ for 4 hours to obtain a dried system; add the dried system to a high-speed mixer, add 5-8 parts of modified nano titanium dioxide, maintain the speed at 500-600 rpm, and stir for 5 minutes to obtain a mixture; add 8-12 parts of composite inorganic pigment to the mixture, maintain the speed at 300-400 rpm, and stir for 10 minutes to obtain a mixed system.

[0023] Preferably, the preparation of modified nano-titanium dioxide includes the following steps:

[0024] By mass, 10 parts of nano-titanium dioxide were dispersed in 50 parts of 95% ethanol aqueous solution, the pH of the system was adjusted to 5 with acetic acid, and the mixture was stirred in a magnetic stirrer at 50°C for 3 hours to obtain an inorganic dispersion; 1 part of KH-570 was slowly added to the inorganic dispersion, and the mixture was reacted at 80°C for 2 hours to obtain a modified system; the modified system was dried and ground to obtain modified nano-titanium dioxide;

[0025] The present invention also provides a high light transmittance, weather-resistant and impact-resistant colored striped plate, which consists of a weather-resistant layer, a substrate layer and a weather-resistant layer from top to bottom. The striped layer is injected between the weather-resistant layer and the substrate layer to form a uniform and parallel striped pattern that runs through the interface between the weather-resistant layer and the substrate layer, giving the plate a visual effect of colored stripes.

[0026] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0027] 1. This invention utilizes the blending of PC and PBAT, with the aid of tetrabutyl titanate to promote interfacial compatibility and form a chemically bonded copolymer, significantly improving the rigidity of the matrix layer. During the melting process, the micro-crosslinking of the initiator further enhances the interlayer bonding force. Compared with the prior art, this invention avoids the defects of insufficient toughness in rigid materials through MBS and multilayer structure design. Subsequent processing releases internal stress, improves molecular chain arrangement, reduces microcracks, and ensures that the material maintains excellent rigidity under high loads. It is suitable for high-strength applications such as building decoration and automotive interiors.

[0028] 2. This invention uses MBS as a toughening agent, and the flexibility of PBAT and the rigidity of PC work synergistically. Combined with tetrabutyl titanate to improve interfacial compatibility, stress concentration is avoided. Compared with the prior art, this invention enhances energy absorption and dispersion capabilities through multilayer structure and interlayer crosslinking induced by DCP. Online annealing and slow cooling processes further optimize the molecular chain arrangement, enabling the sheet to exhibit excellent toughness under impact load.

[0029] 3. This invention, through the composite weather-resistant layer of PMMA and PC, and the stripe layer design of modified nano-titanium dioxide and composite inorganic pigments, achieves significantly better light transmittance than traditional colored striped panels; the multi-channel distributor forms a uniform and delicate stripe pattern, reducing light scattering; the step-by-step mixing process ensures uniform dispersion of nanofillers and avoids agglomeration; maleic anhydride grafted onto PC improves compatibility and reduces micro-phase separation; through the synergistic effect of components and processes, it balances high light transmittance and the visual effect of colored stripes, making it suitable for the field of transparent decorative panels.

[0030] 4. This invention utilizes the synergistic effect of UV-326, UV-1600, and HALS in the weather-resistant layer to cover a wide ultraviolet band, inhibiting photo-oxidation reactions and resulting in superior weather resistance compared to traditional PC sheets. Furthermore, the composite matrix of PMMA and PC provides high transparency and weather resistance, protecting the stripe layer and matrix layer from UV degradation. The slow cooling process optimizes the molecular chain arrangement, reduces internal stress, and minimizes microcracks during the aging process. Through the multi-layered structure and the synergistic effect of additives, the mechanical stability of the sheet under xenon arc lamp aging is significantly improved, making it suitable for long-term exposure environments such as outdoor decoration.

[0031] 5. This invention uses composite inorganic pigments uniformly mixed in a ball mill, combined with modified nano-titanium dioxide, resulting in a color difference variation far lower than that of traditional organic pigment boards. Furthermore, KH-570 modification enhances the compatibility of nano-titanium dioxide with weather-resistant PC, reducing agglomeration and ensuring stripe uniformity. A multi-channel distributor forms a fine stripe pattern, improving color stability. UV absorbers and HALS inhibit photo-oxidation reactions, protecting the pigments from degradation. Compared to existing technologies, this invention significantly improves color fastness through inorganic pigment and process optimization, making it suitable for applications requiring high aesthetic appeal and long-term color stability. Attached Figure Description

[0032] Figure 1 The graphs show the changes in tensile strength of the colored striped plates prepared in Examples 1-3 and Comparative Examples 13-16 before and after aging. Detailed Implementation

[0033] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0034] The polycarbonate of this invention has a Tg of 150℃ and a melt index of 10 g / 10 min; PBAT is polybutylene terephthalate-adipate, with a processing temperature of 180-230℃ and a melt index of 5-10 g / 10 min; PMMA is polymethyl methacrylate, with a processing temperature of 180-250℃ and a melt index of 6-8 g / 10 min; MBS is a core-shell toughening agent for methyl methacrylate-butadiene-styrene copolymer; and maleic anhydride... The grafting rate of maleic anhydride in the grafted polycarbonate is 1-2%; the particle size of nano titanium dioxide is 20-50nm; the polyether dispersant is BYK-310; HALS is a hindered amine light stabilizer, CAS number 82451-48-7; UV-326 is a triazole ultraviolet absorber, CAS number 3896-11-5; UV-1600 is a triazine ultraviolet absorber, CAS number 204583-39-1. All raw materials used are commercially available products.

[0035] Please see Figure 1 This invention provides a high-transmittance, weather-resistant, and impact-resistant colored striped plate and its manufacturing method. The technical solution is as follows:

[0036] Example 1

[0037] By weight, 80 parts of polycarbonate and 20 parts of polybutylene terephthalate (PET) were placed in a vacuum drying oven and dried at 80°C for 4 hours to obtain a dried raw material. The dried raw material was then added to a twin-screw extruder, along with 0.4 parts of tetrabutyl titanate. The melt temperature was 250-260°C, the screw speed was 250 rpm, and the mixture was melt copolymerized for 20 minutes to obtain a copolymer. 8 parts of MBS, 0.3 parts of antioxidant 1010, and 0.5 parts of zinc stearate were added to the copolymer, and the screw speed was maintained at 400 rpm to obtain the matrix layer.

[0038] 60 parts of polymethyl methacrylate and 40 parts of polycarbonate were placed in a vacuum drying oven and dried at 90°C for 4 hours to obtain a dried material. The dried material was then added to a twin-screw extruder, along with 4 parts of maleic anhydride-grafted polycarbonate, 0.5 parts of UV absorber-326, 0.5 parts of UV absorber 1600, 0.8 parts of HALS, and 0.5 parts of zinc stearate. The screw speed was maintained at 300 rpm to obtain a weather-resistant layer.

[0039] Ten parts of nano-titanium dioxide were dispersed in 50 parts of 95% ethanol aqueous solution, the pH of the system was adjusted to 5 with acetic acid, and the mixture was stirred in a magnetic stirrer at 50°C for 3 hours to obtain an inorganic dispersion; 1 part of KH-570 was slowly added to the inorganic dispersion, and the mixture was reacted at 80°C for 2 hours to obtain a modified system; the modified system was dried and ground to obtain modified nano-titanium dioxide.

[0040] 80 parts of weather-resistant PC were placed in a vacuum drying oven and dried at 80°C for 4 hours to obtain a dried system. The dried system was then added to a high-speed mixer, along with 6 parts of modified nano-titanium dioxide. The mixture was stirred at 600 rpm for 5 minutes to obtain a mixture. 10 parts of composite inorganic pigment were added to the mixture, and the mixture was stirred at 400 rpm for 10 minutes to obtain a mixed system. 0.6 parts of polyether dispersant, 0.5 parts of zinc stearate, and 0.3 parts of antioxidant 1010 were added to the mixed system. The mixture was then added to a twin-screw extruder, and the screw speed was maintained at 300 rpm to obtain a striped layer. The composite inorganic pigment was obtained by mixing titanium dioxide and iron oxide red at a mass ratio of 1:1. The mixing process was carried out using a ball mill, maintaining a ball-to-material ratio of 10:1, a ball milling speed of 400 rpm, and a ball milling time of 3 hours.

[0041] From top to bottom, the layers are a weather-resistant layer, a base layer, and another weather-resistant layer. The base layer is fed into the main extruder, the weather-resistant layer into the planetary extruder, and the striped layer into the mini extruder. At the end of the homogenization section of the main extruder, dicumyl peroxide initiator is precisely injected via a metering pump at a rate of 0.15% of the total mass of the base layer. The three main melts (weather-resistant layer, base layer, and weather-resistant layer) are then fed into a multi-channel distributor to form a three-layer structure. Simultaneously, the striped layer melt is divided into multiple streams by the distribution channels within the distributor, which are injected into the weather-resistant layer melt and the base layer melt, respectively. A composite melt is obtained from the layered melt; the composite melt is fed into a die head and kept at a temperature to obtain a multi-layered melt; the multi-layered melt is fed into a three-roll calender, with the temperatures of the three rolls controlled at 110℃, 125℃, and 130℃ respectively. The thickness of the sheet is precisely controlled by the gap between the rolls, and preliminary shaping and cooling are performed to obtain the sheet precursor; the sheet precursor is passed through an online annealing furnace, slowly heated to 130℃, and held for 30 minutes; then slowly cooled to below 60℃ at a cooling rate of 1.5℃ / min, and air-cooled to room temperature to obtain a colored striped sheet.

[0042] Examples 2-5 follow the same preparation method and parameter conditions as Example 1, with differences shown in Table 1.

[0043] Table 1. Parameter variations in Examples 1-5

[0044]

[0045]

[0046] Comparative Example 1 is the same as Example 1, except that PBAT is not added to the matrix layer, while other components remain unchanged.

[0047] Comparative Example 2 is the same as Example 1, except that MBS is not added to the matrix layer, while other components remain unchanged.

[0048] Comparative Example 3 is the same as Example 1, except that PBAT and MBS are not added to the matrix layer, and polycarbonate is used directly as the matrix layer.

[0049] Comparative Example 4 is the same as Example 1, except that tetrabutyl titanate is not introduced during the melting process of the substrate layer, and the mixture is directly melted and mixed.

[0050] Comparative Example 5 is the same as Example 1, except that it does not undergo slow cooling during the annealing process.

[0051] Comparative Example 6 is the same as Example 1, except that dicumyl peroxide is not injected during the extrusion process of the main extruder.

[0052] Comparative Example 7 is the same as Example 1, except that a multi-layer structure is not used. The base layer, weather-resistant layer and stripe layer are directly melt-blended and then post-processed to obtain a colored striped plate.

[0053] Experiment Example 1 Mechanical Property Testing

[0054] The colored striped plates prepared in Examples 1-5 and Comparative Examples 1-7 were subjected to mechanical property tests. The tensile strength was tested according to GB / T1040-2018 and the impact strength was tested according to GB / T 1843-2008. The test results are shown in Table 2.

[0055] Table 2 Performance test results of the examples and comparative examples

[0056] Example 1 65.5 56.8 Example 2 65.2 56.5 Example 3 65.4 56.6 Example 4 65.1 56.2 Example 5 65.3 56.4 Comparative Example 1 68.2 42.6 Comparative Example 2 66.8 40.7 Comparative Example 3 70.5 38.5 Comparative Example 4 58.6 41.8 Comparative Example 5 54.6 39.6 Comparative Example 6 58.2 41.2 Comparative Example 7 54.8 36.9

[0057] As shown in Table 2, the mechanical properties of the colored striped plates prepared in the comparative examples differed significantly from those in the examples due to adjustments in components and changes in the process. In Comparative Examples 1-3, the absence of PBAT resulted in a relative increase in the content of rigid polycarbonate, leading to a slight increase in tensile strength, but a significant decrease in toughness and impact strength. The lack of MBS prevented the matrix layer from effectively absorbing and dispersing impact energy, resulting in severe stress concentration and a sharp decline in impact strength. Furthermore, the absence of both PBAT and MBS, two toughening modifiers, meant that while polycarbonate as the matrix layer possessed high tensile strength and stiffness, its notch sensitivity was high, its toughness was poor, and its impact strength was significantly reduced. Combined with Comparative Example 7, the direct melt blending without multilayer treatment disrupted the orderliness of the layered structure, leading to uneven dispersion of functional components in the weather-resistant and striped layers, reducing the material's surface protection and internal toughening effect. Additionally, the blending process may have reduced component compatibility, resulting in phase separation. In Comparative Example 4, tetrabutyl titanate, as a coupling agent, can improve the interfacial compatibility between PC, PBAT, and MBS, and promote the cross-linking and copolymerization reaction of molecular chains. Without tetrabutyl titanate, the interfacial bonding of the copolymer is weak, and micro-defects exist inside the material, reducing tensile strength and impact strength. In Comparative Example 6, DCP, as an initiator, can initiate the chemical cross-linking of the matrix layer, weathering layer, and stripe layer in the multilayer composite process, enhancing the interlayer bonding. In addition, DCP can also promote the slight cross-linking of PC molecular chains, improving the material strength. Without DCP, the interfacial bonding is weak, and the composite material is prone to interlayer delamination under stress, reducing the overall mechanical properties. In Comparative Example 5, slow cooling treatment can effectively release the residual stress inside the material and improve the arrangement and crystallinity of molecular chains. Without it, the internal stress concentration of the material will be caused by disordered molecular chain arrangement, reducing the mechanical properties of the material. In addition, too fast cooling rate will cause the surface and internal cooling rates to be inconsistent, generating microcracks, which will further affect tensile strength and impact strength.

[0058] In summary, this invention combines the rigidity of PC, the flexibility of PBAT, and the impact resistance of MBS. Under the action of tetrabutyl titanate, PC and PBAT are chemically bonded to form a copolymer. The resulting matrix layer provides excellent mechanical support and toughness. In addition, the addition of DCP induces micro-crosslinking of the interlayer structure, enhancing the mechanical properties of the matrix. Finally, through the introduction of online annealing and slow cooling processes, a colored striped plate with excellent mechanical properties is obtained through synergistic effects.

[0059] Examples 6-8 follow the same preparation method and parameter conditions as Example 1, with differences shown in Table 3.

[0060] Table 3. Parameter changes in Examples 1 and 6-8

[0061]

[0062] Comparative Example 7 is the same as Example 1, except that a multi-layer structure is not used. The base layer, weather-resistant layer and stripe layer are directly melt-blended and then post-processed to obtain a colored striped plate.

[0063] Comparative Example 8 is the same as Example 1, except that no stripe layer is used, only the base layer and weather-resistant layer are used, and it is melt extruded without the action of a multi-channel distributor.

[0064] Comparative Example 9 is the same as Example 1, except that polymethyl methacrylate is not used in the weather-resistant layer, while the other components remain unchanged.

[0065] Comparative Example 10 is the same as Example 1, except that maleic anhydride-grafted polycarbonate is not added to the weather-resistant layer, while the other components remain unchanged.

[0066] Comparative Example 11 is the same as Example 1, except that no modified nano-titanium dioxide is added to the stripe layer.

[0067] Comparative Example 12 is the same as Example 1, except that the nano-titanium dioxide in the striped layer is not modified.

[0068] Comparative Example 13 is the same as Example 1, except that the striped layer is not processed by a multi-channel distributor, but is directly melt-extruded by multiple extruders to obtain a colored striped plate.

[0069] Comparative Example 14 is the same as Example 1, except that the composite inorganic pigment is replaced with an organic pigment, while the amount remains the same.

[0070] Comparative Example 15 is the same as Example 1, except that the striped layer is not mixed stepwise using a high-speed mixer during preparation.

[0071] Experiment Example 2: Light Transmittance Test

[0072] The colored striped plates prepared in Examples 1, 6-8, and Comparative Examples 7-15 were subjected to light transmittance tests. The light transmittance was tested according to the test method of GB / T 2410-2008, and the measurement was performed at a wavelength of 550 nm using a light transmittance meter. The sample thickness was uniformly 3 mm. The test results are shown in Table 4.

[0073] Table 4. Test results of the examples and comparative examples

[0074] Example 1 85.6 Example 6 85.4 Example 7 85.3 Example 8 85.5 Comparative Example 7 72.5 Comparative Example 8 88.2 Comparative Example 9 78.5 Comparative Example 10 80.3 Comparative Example 11 90.4 Comparative Example 12 76.8 Comparative Example 13 73.4 Comparative Example 14 70.9 Comparative Example 15 74.2

[0075] As shown in Table 4, the comparative examples, through adjustments to components and changes in the process, exhibited significantly different light transmittance properties compared to the examples. In Comparative Example 7, direct melt blending disrupted the layered structure of the matrix layer, weather-resistant layer, and stripe layer, resulting in blurred material interfaces. The nano-titanium dioxide and pigments in the stripe layer were dispersed throughout the entire plate, leading to enhanced light scattering and a significant decrease in light transmittance. In Comparative Example 8, the matrix layer and weather-resistant layer constituted a highly transparent base plate. Without the introduction of a stripe layer, it lacked the visual effect of colored stripes, but it demonstrated the effectiveness of the matrix layer and weather-resistant layer. PMMA itself possesses excellent transparency; in Comparative Examples 9-10, PMMA itself has excellent transparency and weather resistance. Without its introduction, the optical properties of the weather-resistant layer and its compatibility with other additives decrease, leading to microscopic phase separation or reduced transparency, affecting the light transmittance of the sheet. Furthermore, the absence of maleic anhydride-grafted polycarbonate results in severe phase separation during melt blending, forming micron-sized sea-island structures that strongly scatter light, significantly reducing the overall light transmittance of the sheet. In Comparative Examples 11-12, the aesthetic effect of the striped layer depends on modified nano-titanium dioxide; without its introduction, the stripes... The area, mainly composed of PC resin and a small amount of pigment, becomes nearly transparent, losing its contrast with the substrate layer and failing to form clear stripes. Without modified nano-titanium dioxide, severe particle agglomeration occurs, forming large pigment aggregates. This not only makes the stripes rough and uneven but also becomes a light scattering center, significantly reducing the material's transmittance. In Comparative Example 13, the core function of the multi-channel distributor is to divide the melt of the striped layer into multiple fine "streams" and evenly inject them between the weathering layer and the substrate layer, thereby forming a fine, parallel striped pattern. Without this distributor, the striped layer melt would only form... The formation of one or more coarse, irregular color bands results in a rough overall appearance, uneven light transmission, and a significant reduction in light transmittance. In Comparative Example 14, the organic pigments exhibit poor optical stability and are less compatible with the PC matrix than composite inorganic pigments. Furthermore, they are prone to decomposition and discoloration during melt extrusion, thus affecting the color stability and light transmittance of the product. In Comparative Example 15, the direct mixing method allows nano-titanium dioxide to be easily encapsulated by other pigment particles, forming agglomerates and preventing uniform nanoscale dispersion. Uneven dispersion directly leads to a deterioration in the optical performance of the stripe layer, thereby reducing the light transmittance of the board.

[0076] In summary, at the component level, this invention ensures the mechanical properties and basic transparency of the sheet by employing a toughened polycarbonate system; it uses PMMA and PC in synergy, with maleic anhydride-grafted polycarbonate as a compatibilizer, to form a highly transparent, weather-resistant layer; finally, the addition of modified nano-titanium dioxide and composite inorganic pigments forms a striped layer; at the process level, the striped layer is prepared using a step-by-step mixing process to ensure that the nanofillers are fully and uniformly dispersed in the resin; a multi-channel distributor is used to divide and precisely inject the striped layer melt, forming a fine, uniform, parallel striped pattern, reducing light scattering; and the synergistic effect of multiple mechanisms between components and processes improves the light transmittance of the sheet.

[0077] Comparative Example 13 is the same as Example 1, except that the striped layer is not processed by a multi-channel distributor, but is directly melt-extruded by multiple extruders to obtain a colored striped plate.

[0078] Comparative Example 14 is the same as Example 1, except that the composite inorganic pigment is replaced with an organic pigment, while the amount remains the same.

[0079] Comparative Example 15 is the same as Example 1, except that the striped layer is not mixed stepwise using a high-speed mixer during preparation.

[0080] Comparative Example 16 is the same as Example 1, except that no UV absorber and HALS are introduced into the weather-resistant layer, while the other components remain unchanged.

[0081] Comparative Example 17 is the same as Example 1, except that only UV absorber-326 and HALS are added to the weather-resistant layer, while the other components remain unchanged.

[0082] Comparative Example 18 is the same as Example 1, except that the striped layer uses the same polycarbonate as the base layer and the weather-resistant layer, and does not use weather-resistant PC.

[0083] Experimental Example 3: Weather Resistance and Color Fastness Test

[0084] The colored striped plates prepared in Examples 1-5 and Comparative Examples 13-18 were subjected to weathering resistance and color fastness tests, according to GB / T 16422.2-2014, using a xenon arc lamp aging chamber with an irradiation intensity of 0.51 W / (m²). 2 The light intensity was measured at 340 nm / nm, with a cycle mode of 102 min light exposure (without water spray) + 18 min light exposure (with water spray). The blackboard temperature was 65±3℃, the relative humidity was 50±5%, and the aging time was 1000 h. The tensile strength change before and after aging was tested according to GB / T 1040-2018. The color difference value before and after aging was measured using a colorimeter according to GB / T 7921-2008. The test results are shown in Table 5. The tensile strength changes before and after aging of the colored striped plates prepared in Examples 1-3 and Comparative Examples 13-16 are shown in Table 5. Figure 1 As shown.

[0085] Table 5. Test results of the examples and comparative examples

[0086]

[0087] Through Table 5, Figure 1 The results show that, compared with the examples, the weather resistance and color fastness of the prepared colored striped plates obtained by adjusting the components and changing the process in the comparative examples are significantly different. In Comparative Example 13, the absence of a distributor resulted in a macroscopic, thick, and blurred layered structure between the striped layer and the substrate layer. Under thermal stress or UV aging, due to the differences in the thermal expansion coefficients and aging rates between different materials, stress concentration easily occurs at the interface, leading to delamination and cracking, thus significantly reducing the tensile strength of the material. In addition, uneven stripes also lead to a visually mottled appearance and more obvious local fading, increasing the overall color difference. In Comparative Example 14, inorganic pigments have excellent lightfastness, heat resistance, and chemical stability. Although organic pigments have bright colors, the chromophores such as conjugated double bonds in their molecular structure are easily destroyed under UV light and heat-oxygen environments, leading to chemical degradation and fading, resulting in a significant increase in color difference. In Comparative Example 15, without stepwise mixing, nano-titanium dioxide and pigments will agglomerate. Aggregates not only cause uneven color and color spots, but also become stress concentration points within the material. Under external force or during aging, they are prone to initiating and propagating microcracks, reducing overall performance. In Comparative Examples 16-17, the role of the UV absorber is to absorb high-energy ultraviolet light and convert it into harmless heat energy; the light stabilizer interrupts the chain reaction by capturing free radicals generated during polymer degradation. Without these two key additives, ultraviolet light will directly act on the polymer long chain, initiating photo-oxidation and photo-degradation reactions, leading to molecular chain breakage, material brittleness, yellowing, and fading. Through synergistic effects, the UV absorption spectrum range and efficiency are improved. In Comparative Example 18, the use of ordinary PC leads to insufficient stability of the stripe layer itself. During long-term aging, the stripe layer degrades and discolors faster than weather-resistant PC. This not only affects the overall color fastness, but its degradation also destroys the interfacial bonding with the surrounding materials, potentially causing interfacial separation and reducing the overall mechanical properties of the material.

[0088] In summary, this invention achieves comprehensive UV absorption by covering different UV bands with UV-326 and UV-1600; HALS captures free radicals generated by photo-oxidation, inhibiting chain reactions; the composite matrix of polymethyl methacrylate and polycarbonate provides high transparency and weather resistance, jointly protecting the stripe layer pigments and the matrix layer; in addition, the composite inorganic pigments are uniformly mixed through a ball mill, providing excellent UV shielding and color stability; modified nano-titanium dioxide undergoes KH-570 surface treatment, enhancing compatibility with weather-resistant PC, reducing agglomeration, and improving dispersion uniformity; furthermore, through stepwise mixing and multi-channel distribution processes, the synergistic effect of components and processes ensures the stability and aesthetics of the colored striped plate under long-term aging.

[0089] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for manufacturing a high-transmittance, weather-resistant, and impact-resistant colored striped plate, characterized in that, The manufacturing process includes the following steps: From top to bottom, the layers are a weather-resistant layer, a base layer, and another weather-resistant layer. The base layer is added to the main extruder and melt-extruded to obtain the base layer melt. The weather-resistant layer is added to the satellite extruder and melt-extruded to obtain the weather-resistant layer melt. The striped layer is added to the small extruder and melt-extruded to obtain the striped layer melt. At the end of the homogenization section of the main extruder, dicumyl peroxide is precisely injected as an initiator through a metering pump at a dosage of 0.15% of the total mass of the base layer. The weather-resistant layer melt, the base layer melt, and the weather-resistant layer melt are then fed into a multi-channel distributor to form a three-layer structure. Simultaneously, the striped layer melt is divided into multiple streams by the distribution channels within the distributor, which are injected into the weather-resistant layer melt and the base layer melt respectively to obtain a composite melt. The composite melt is then fed into the die and undergoes a post-processing process to obtain the colored striped plate. The striped layer is embedded in the upper and lower weather-resistant layers in the form of 8-12 streams, with an embedding depth of 1 / 3 of the thickness of the weather-resistant layer; the flow rate is precisely controlled at 0.5-1.0 kg / h by a metering pump; each stream is injected into the interface of the weather-resistant layer / the substrate layer at an angle of 15-30° through the nozzle of the distribution channel; the stripe width is precisely controlled to be 1-3 mm and the spacing to be 5-10 mm by the microporous channel of the distributor and the nozzle design to ensure a uniform decorative effect; wherein the weather-resistant layer is 0.5-1.0 mm thick and the substrate layer is 2-3 mm thick; The manufacturing of the matrix layer includes the following steps: placing polycarbonate and polybutylene terephthalate in a vacuum drying oven and drying to obtain a dried raw material; adding the dried raw material to a twin-screw extruder, adding tetrabutyl titanate, and melt copolymerizing to obtain a copolymer; adding MBS, antioxidant 1010, and zinc stearate to the copolymer, and melt extruding to obtain the matrix layer; The weather-resistant layer is manufactured by the following steps: placing polymethyl methacrylate and polycarbonate in a vacuum drying oven and drying them to obtain a dried material; adding the dried material to a twin-screw extruder, adding maleic anhydride-grafted polycarbonate, UV absorber-326, UV absorber 1600, HALS and zinc stearate, and melt-extruding to obtain a weather-resistant layer; The striped layer is manufactured by the following steps: placing weather-resistant PC in a vacuum drying oven and drying it to obtain a dried system; adding the dried system to a high-speed mixer, adding modified nano-titanium dioxide, and stirring to obtain a mixture; adding a composite inorganic pigment to the mixture and stirring to obtain a mixed system; adding a polyether dispersant, zinc stearate, and antioxidant 1010 to the mixed system, adding it to a twin-screw extruder, and melt-extruding to obtain a striped layer; wherein the composite inorganic pigment is obtained by mixing titanium dioxide and iron oxide red in a certain mass ratio.

2. The method for manufacturing a high-transmittance, weather-resistant, and impact-resistant colored striped plate according to claim 1, characterized in that, The post-processing procedure includes the following steps: The composite melt enters the die head and is heat-treated to obtain a multi-layer melt. The multi-layer melt is then fed into a three-roll calender, where the thickness of the sheet is precisely controlled by the gap between the rollers, and preliminary shaping and cooling are performed to obtain the sheet precursor. The sheet precursor is then passed through an online annealing furnace for heat treatment, followed by cooling treatment and air cooling to room temperature to obtain the colored striped sheet.

3. The method for manufacturing a high-transmittance, weather-resistant, and impact-resistant colored striped plate according to claim 1, characterized in that, The preparation of the modified nano-titanium dioxide includes the following steps: Nano-titanium dioxide was dispersed in a 95% ethanol aqueous solution, the pH of the system was adjusted with acetic acid, and the mixture was stirred in a magnetic stirrer to obtain an inorganic dispersion; KH-570 was added to the inorganic dispersion, and a modification reaction was carried out to obtain a modified system; the modified system was dried and ground to obtain the modified nano-titanium dioxide.

4. A high-transmittance, weather-resistant, and impact-resistant colored striped plate, characterized in that: The colored striped plate consists of a weather-resistant layer, a substrate layer, and a weather-resistant layer from top to bottom, wherein the stripe layer is injected between the weather-resistant layer and the substrate layer to form a uniform and parallel stripe pattern; the high-transmittance, weather-resistant, and impact-resistant colored striped plate is prepared by the manufacturing method described in any one of claims 1-3.

Citation Information

Patent Citations

  • High-impact-resistant polycarbonate / polylactic acid resin composition and preparation method thereof

    CN111087789A

  • PC / PMMA alloy as well as preparation method and application thereof

    CN112063146A

  • High-weather-resistance polycarbonate striped plate and preparation method thereof

    CN120287686A